Consolidation around a point heat source (correction and verification). (13th September 2019) - Chaudhry, Aqeel Afzal; Buchwald, Jörg; Kolditz, Olaf; Nagel, Thomas
Summary: We provide a brief review of the results obtained by Booker and Savvidou in their original 1985 paper describing the consolidation around a point heat source embedded in a fluid‐saturated porous medium. Although it gained a lot of attention in recent years, mainly as a benchmark problem for numerical codes, the analytical expressions for normal and shear stresses could not be confirmed to be correct. In this manuscript, we verify the expressions for temperature, pressure, and displacement and derive new expressions for the stress tensor withstanding numerical verification using the scientific open‐source thermo‐hydro‐mechanical‐chemical (THMC) simulator OpenGeoSys.